2018
DOI: 10.2174/1381612824666180924102530
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian PER2 Enhancer Nobiletin Reverses the Deleterious Effects of Midazolam in Myocardial Ischemia and Reperfusion Injury

Abstract: Background: Recently, we identified the circadian rhythm protein Period 2 (PER2) in robust cardioprotection from myocardial ischemia (MI). Based on findings that perioperative MI is the most common major cardiovascular complication and that anesthetics can alter the expression of PER2, we hypothesized that an anesthesia mediated downregulation of PER2 could be detrimental if myocardial ischemia and reperfusion (IR) would occur. Methods and Results: We exposed mice to pentobarbital, fentanyl, ketamine, propof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Indeed, our group found that nobiletin induces cardiac Per2 and provides a cardioprotective effect from myocardial IR injury in a Per2-dependent manner. Furthermore, we demonstrated that the deleterious effects on the heart of the commonly-prescribed benzodiazepine midazolam can be rescued when nobiletin is administered prior to myocardial IR-injury [208]. Our studies are in line with other groups targeting nuclear receptors, in particular REV-ERBs, as a promising strategy in the context of cardiac IR-injury.…”
Section: Circadian Disruption At the Root Of Disease And Circadian Cosupporting
confidence: 77%
“…Indeed, our group found that nobiletin induces cardiac Per2 and provides a cardioprotective effect from myocardial IR injury in a Per2-dependent manner. Furthermore, we demonstrated that the deleterious effects on the heart of the commonly-prescribed benzodiazepine midazolam can be rescued when nobiletin is administered prior to myocardial IR-injury [208]. Our studies are in line with other groups targeting nuclear receptors, in particular REV-ERBs, as a promising strategy in the context of cardiac IR-injury.…”
Section: Circadian Disruption At the Root Of Disease And Circadian Cosupporting
confidence: 77%
“…Moreover, our in vivo and in vitro studies suggest that light-elicited transcriptional reprogramming of endothelial cells protects endothelial barrier function during IR injury. Together with previous studies on myocardial IR injury (Yang et al, 2016), these studies highlight the importance of cardiac endothelia in IR injury and point toward unrecognized therapeutic strategies for cardiovascular disease using intense light or pharmacological compounds, such as the circadian rhythm enhancer nobiletin (Gile et al, 2018; Oyama et al, 2018), to increase the amplitude of endothelial PER2. Despite this strong evidence, our studies are limited to analysis of endothelia-specific PER2-deficient mice; thus, the contribution of other cardiac cells cannot be fully excluded (Seo et al, 2015).…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, our in vivo and in vitro studies suggest that light elicited reprogramming of endothelial metabolism protects the endothelial barrier function during IR-injury. Together with previous studies on myocardial IR-injury (Yang et al, 2016), these studies highlight the importance of cardiac endothelial metabolism in IR-injury and point towards unrecognized therapeutic strategies for cardiovascular disease using intense light or pharmacological compounds, such as the circadian rhythm enhancer nobiletin Oyama et al, 2018), to increase endothelial PER2 amplitude.…”
Section: Discussionsupporting
confidence: 62%